Flexural Behaviour of RC Beams Strengthened with Prestressed CFRP NSM Tendon Using New Prestressing System - Woo-tai Jung; Jong-sup Park; Jae-yoon Kang; Moon-seoung Keum; Young-hwan Park (International Journal of Polymer Science)
CFRP has been used mainly for strengthening of existing structures in civil engineering area. Prestressed strengthening is being studied to solve the bond failure model featuring EBR and NSMR methods. The largest disadvantage of the prestressing system is that the system cannot be removed until the filler is cured. This problem lowers the turning rate of the equipment and makes it limited to experiment, which stresses the necessity of a new prestressing system. Therefore, the present study applies a new prestressing system which reliefs the need to wait until the curing of the filler after jacking to the prestressing of NSMR and examines the effect of the prestressing size and location of the anchorage on the strengthened behaviour. The experimental results show that the crack and yield loads increase with higher level of prestress, while the ductility tends to reduce, and the anchor plate should be installed within the effective depth ds to minimize the occurrence of shear-induced diagonal cracks. The comparison of the experimental results and results by section analysis shows that the section analysis could predict the maximum load of the specimens strengthened by prestressed NSMR within an error between 4% and 6%.